Teachers’ lack of deeper analytical reflections: who is to blame? - Otienoh, Ruth Ombonya (My University, 2011)
Reflective practice through journal writing is among the concepts that are introduced to teachers by my institution during the six-month long Certificate in Education Programmes (CEPs). The objective is to enable teachers to develop professionally by learning from their own practice after completion of the programmes. However, this can only occur if teachers are able to critically analyse issues, events and situations within their practice. Over the years, it has been realised that most teachers are unable to critically reflect. This study was of a qualitative hermeneutic phenomenological nature. The sample included eight CEP graduate teachers and four facilitators of the programmes. Semi-structured interviews were the sole method of data collection. The study established that apart from the way reflective practice is introduced to the teachers, other factors such as language, teachers’ attitude and their lack of capacity are responsible for how they understand reflective practice, thus impacting on how they write their reflections in their journals.
Keywords: Journal; Reflective practice; Certificate in Education Programmes (CEPs)